ITIKAD BAIK SEBAGAI TOLAK UKUR PERBUATAN DEBITOR DALAM KEPAILITAN - Lucky Dafira Nugroho (Faculty of Law - Tarumanagara University, 2017)
Good faith that has a dual role as the principle and norm experience a shift from specialized legal principle into common legal principle. The shift in question are familiar in good faith in some areas of the law as a guide to carry out obligations by the parties with honesty and faithfull. The good faith needs to let the foundation of the examiners over the deeds of the debtor in bankruptcy. Based upon these problems can get legal issues about the characteristics of good faith as a guide in judging the deeds of the law of the debtor in the bankruptcy context. Over the subsequent legal issues are examined by using the normative legal research methods. Upon such research can pull the conclusion that characteristics of good faith, framed within the concept of honesty and propriety of the moral teachings sourced. In the moral teachings of each man was ordered to do the Act of not harming others. Principle of good faith in law Bankruptcy and suspension of payment set forth in the provision concerning the expiry of the delay of debt payment obligations and implicitly in the approved actio pauliana lawsuit can. Assessment in good faith it is indispensable in the process of examination of the application for bankruptcy, suspension of payment application, requests for peace by the debtor, and actio pauliana lawsuit. Characteristic of good faith in bankruptcy indicates that the principle of good faith (bonafides/good faith) are also set forth in the provisions of the law on Bankruptcy and debt payment suspension.Keywords: Good Faith, Debtor Performance, Bankruptcy